Fingertip Heartbeat Monitor - ZAKARIA, MUHAMMAD AFIQ (Progress in Engineering Application and Technology, 2021)
In preventing cardiac-related disorders, heart rate monitoring is very important. Uncovering cardiac difficulties early on can lead to death. This problem is caused by the lack of instruments to quickly detect cardiac problems and the warning of anxiety patients. A MAX 30100 connected to a smartphone via Bluetooth will be used as the proposed system. The processed signals are transmitted to your mobile phone. This will allow patients to receive early treatment and prevention and hopes to reduce the rate of death from heart problems.